Rapid Assessment of Roadsides as Potential Habitat for Monarchs and Other Pollinators - Cariveau, Alison B.; Anderson, Erik; Baum, Kristen A.; Hopwood, Jennifer; Lonsdorf, Eric; Nootenboom, Chris; Tuerk, Karen; Oberhauser, Karen; Snell-Rood, Emilie (Frontiers in Ecology and Evolution, 2019)
Sustaining native pollinator populations and reversing declines in species such as the monarch butterfly (Danaus plexippus) will require enhancing and maintaining habitats across many regions and land use sectors. Rights-of-way, such as the areas surrounding roads, have long been regarded as important habitat for pollinators due to their ubiquitous nature and management for herbaceous species including nectar plants and larval host plants. With better information regarding the quality of pollinator habitat in roadside rights-of-way, managers can identify the location of potential habitat and evaluate the effects of management activities. We conducted a survey of roadside managers to determine needs and limitations related to assessing and managing rights-of-way as monarch habitat. Survey results indicated that managers are often limited by time, funding, and expertise in plant identification. Based on survey results and consultations with roadside managers, we developed a protocol for rapid assessment of roadside rights-of-way (hereafter, Rapid Assessment) that can be easily implemented by managers and is flexible based on the expertise of the observer and the data needs of the roadside management authority. Using readily available software, the field data are automatically processed through a Roadside Monarch Habitat Evaluator to generate habitat quality scores that may be used by managers to describe the habitat resources and to inform management strategies. We field-tested the protocol at roadsides in Minnesota and compared results with a more intensive protocol for monarch habitat monitoring (the Integrated Monarch Monitoring Program). We found that the Rapid Assessment provided similar data as the more intensive protocol regarding milkweed densities, nectar plant species richness, and monarch use of sites (eggs and larvae, when detection levels were sufficient). Observed high habitat values in roadside rights-of-way confirm the potential of such habitat for pollinator and monarch conservation.